Nontariff measures with market imperfections trade and welfare implications - Beghin, John C. 1954-; Beladi, Hamid (Emerald, 2013)
This volume presents new developments in non-tariff measure (NTM) policy analysis by leading authors in the field; from conceptual developments and methodology improvements, to a series of innovative cases studies. A novel policy research agenda underlies the book recognizing that some NTMs are required to sustain market exchange. The investigations address the welfare and trade impacts of standard-like NTMs in presence of market imperfections, their measurements, potential protectionism, and implications for North-South trade and income prospects in developing countries, including for small holders. Several analyses address the potential trade-cost effects of these NTMs through their lack of transparency, their heterogeneity across countries, and constraints to harmonize them and gains from harmonization. Several analyses investigate trade within OECD countries, including looking at export decisions by heterogeneous firms and the effect of harmonization of standards on firm productivity, and exploring the export-enhancing effect of a countrys own stringency in standards. Practical policy implications are drawn.
Keywords: Non-tariff trade barriers.; Foreign trade regulation.; elektronické knihy; electronic books